HERBAL REMEDIES FOR ORAL HYGIENE USED IN KARACHI, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Objective: Studies showed that periodontal problems are increasing day by day worldwide among the elders, youngsters and especially the children due to more consumption of sugary food and improper oral hygienic habits. Dental caries, mucosal lesions and periodontal illnesses are the fast growing periodontal diseases. Various medications are available for treatment but now people are seeking herbal remedies due to easy availability, low cost and less side effects. Healthcare professionals also suggest herbal remedies for less severe disorders due to increasing antibiotic resistance. The intent of the study is to investigate the use of herbal remedies for oral hygiene used in Karachi, Pakistan.Methodology: A comprehensive search of three electronic databases (Google Scholar, Pub Med, and Research Gate) was performed to gather existing research on oral diseases and herbal plants. A survey was conducted among 119 oral disorder patients in Karachi to gather information on the herbal plants they use for oral hygiene. The survey included 10 herbal plant options. Research followed a structured methodology for the systematic review including citation screening, data extraction and validation. However, we were not able to conduct a meta-analysis due to the descriptive statistics.Results: A study of 119 participants found that 93.3% believe herbal remedies work for oral hygiene and 60.5% use them. Common oral diseases reported included herpangina, dental caries and gingivitis, with 63.6% experiencing bad breath, while many participants had habits that could harm oral health. 73.9% used mouthwash and the top herbal remedies used were Eucalyptus leaf, S.aromaticum, A.indica and Cinnamon bark. However 6.7% reported allergic reactions to herbal remedies.Conclusions: Herbal medicines such as Eucalyptus, S.aromaticum and Cinnamon are popular for oral hygiene among patients with oral disorders but further study is needed to validate their efficacy and safety.